PERILAKU AKTIVITAS FISIK TERHADAP KEJADIAN GIZI LEBIH PADA ANAK USIA SEKOLAH DASAR DI SDN 018 DESA KUBANG JAYA KABUPATEN KAMPAR TAHUN 2018 - RAHMI NOVALINA; Zahtamal Zahtamal; Yuyun Priwahyuni (STIKes Al-Insyirah Pekanbaru, 2019)
Over nutrition is the condition of person’s body when the amount of energy is stored in the form of fat.The age group at risk of developing over nutrition is children of primary school age 6-12 years old. The causes of over nutrition in children can be caused by lack of physical activity, sedentary behavior and mother’s knowledge can also influence. This study aims to determine the relationship of physical activity, sedentary behavior and mother knowledge of the incidence of over nutrition in elementary school children. The type of research used is quantitative analytical. The study design was analytic cross sectional study. The population in this study were all students in grades 4.5 and 6 with total 494 people, the sample in this study were 191 people. Data analysis was carried out by multivariate using logistic regression tests. The results showed low physical activity risked 4.1 times (POR = 3,080-14,473) experienced over nutrition, high sedentary behavior more risk 4,8 times (POR = 2,033-11,406) experienced over nutrition, and low mother’s knowledge riskier 3,1 time (POR = 1,475-6,725) experienced over nutrition. The conclusion in this study is there is a relationship between physical activity, sedentary behavior and knowledge of mothers with the incidence of over nutrition in primary school children. It is recommended for parents to pay more attention to what activities that children have in their spare time so the children do more physical activity than sedentary behavior. It is suggest to the relevant Puskesmas to provide counseling and socialization about excess nutrition in elementary school children.